Calculation and Analysis of the Power Supply of a Railgun From a Magnetohydrodynamic Generator and a Transformer; Journal of Applied Mechanics and Technical Physics; Vol. 59, iss. 2 - Nosov G. V. Gennady Vasilievich; Nosova M. G. Mariya Gennadjevna; Vasiljeva (Vassilyeva) Yu. Z. Yuliya Zakharovna; Kuleshova E. O. Elena Olegovna (2018, 2018)
Title screen